Comparing the Effect of Static and PNF Stretching on Hip Joint Flexibility of Un-training Female Students - Manizeh Mansour Sadeghi; Behnaz Motekalemi; Mitra Poursohrab; Tahmineh Saidi Ziabari; Delaram Sorahi (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2016)
Since many of people in their functional activities mostly place their knee joint in flexed position, the hamstring muscles tend to be shortened. On the other hand, shortness of these muscles affect the knee joint directly and the Hip Joint Flexibility indirectly. The purpose of this study is to compare the effect of static and PNF stretching on hip joint flexibility of un-training female students. Twenty-four 18–30 years old un-training female students without any history of pathology in hip, knee or back were selected. They were divided into three groups with 8 women in each group (static stretch, PNF stretch and control). The two stretch groups received stretching program three days every week for six weeks, while the control group did not. The result shows that range of hip joint flexibility of both groups of static and PNF stretching increased (P < 0.05). However, there was no significant difference between these two groups (P > 0.05). The while it remained unchanged in control subjects (P > 0.05). Employing both methods (static and PNF stretching) increase the hip joint flexibility. The findings of this study suggest that optimal flexibility is achieved with a combination of these two methods. Thus, we recommend the combined training method to athletes who require very high flexibility.